Final report on the Controlled Cold Helium Spill Test in the LHC tunnel at CERN. Issue 1 (November 2015) - Dufay-Chanat, L; Bremer, J; Casas-Cubillos, J; Chorowski, M; Grabowski, M; Jedrusyna, A; Lindell, G; Nonis, M; Koettig, T; Vauthier, N; van Weelderen, R; Winkler, T
Abstract: The 27 km circumference LHC underground tunnel is a space in which the helium cooled LHC magnets are installed. The vacuum enclosures of the superconducting magnets are protected by over-pressure safety relief devices that open whenever cold helium escapes either from the magnet cold enclosure or from the helium supply headers, into this vacuum enclosure. A 3-m long no stay zone around these devices is defined based on scale model studies, protecting the personnel against cold burns or asphyxia caused by such a helium release event. Recently, several simulation studies have been carried out modelling the propagation of the helium/air mixture, resulting from the opening of such a safety device, along the tunnel. The released helium flows vary in the range between 1 kg/s and 0.1 kg/s. To validate these different simulation studies, real life mock-up tests have been performed inside the LHC tunnel, releasing helium flow rates of 1 kg/s, 0.3 kg/s and 0.1 kg/s. For each test, up to 1000 liters of liquid helium were released under standard operational tunnel conditions. The data recorded include oxygen concentration, temperature and flow speed measurements, and video footage used to assess qualitatively the visibility. These measurements have been made in the up- and downstream directions, with respect to the air ventilation flow, of the spill point. This paper presents the experimental set-up under which these release tests were made, the effects of these releases on the atmospheric tunnel condition as a function of the release flow rate. We discuss the modification to the personnel access conditions to the LHC tunnel that are presently implemented as a result of these tests.